2022
DOI: 10.1039/d2nj03121c
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid dehydrogenation by [Ru(η6-benzene)(L)Cl] catalysts: L = 2-methylquinolin-8-olate and quinolin-8-olate

Abstract: The [Ru(η6-benzene)(L)Cl] (complex 1, L = 2-methylquinolin-8-olate and complex 2, L = quinolin-8-olate) complexes were synthesised and employed for the dehydrogenation of the formic acid (FA) in the presence of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…S9 †). [40][41][42] Various concentrations of acid, base and catalyst, as well as various temperatures, were used to investigate the catalyst for dehydrogenation. At a constant temperature of 50 °C, the reaction rate was reliant on the concentration of the substrates and catalysts.…”
Section: Dehydrogenation Of Formic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…S9 †). [40][41][42] Various concentrations of acid, base and catalyst, as well as various temperatures, were used to investigate the catalyst for dehydrogenation. At a constant temperature of 50 °C, the reaction rate was reliant on the concentration of the substrates and catalysts.…”
Section: Dehydrogenation Of Formic Acidmentioning
confidence: 99%
“…manometer, we have evaluated some previously described catalysts under comparable conditions. [40][41][42] A differential manometer is a pressure gauge that shows the disparity between the reference and working portions. Jacketed cells were utilized as the reference and working compartments at constant temperatures.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solakidou 31 et al found that catalytic complexes containing two ligands (phosphine and Schiff-base ligand) were significantly more efficient in producing H 2 from formic acid than 32 They also explain that the hydrogen pressure generated in the presence of triethylamine in isotonic conditions determines the thermodynamic equilibrium and thus the conversion of formic acid. 33 The complexes Ru(Z 6 -benzene)(L)Cl] (complex 1, L = 2methylquinolin-8-olate/complex 2, L = quinolin-8-olate) were synthesized by Vatsa 34 et al for the FADH in the presence of sodium formate (SF). The catalytic activity of the FA/SF solution at different temperatures and concentration ratios was also studied.…”
Section: Fa Decomposition Reaction Pathway Mechanismmentioning
confidence: 99%
“…The complexes Ru­(Z 6 -benzene)­(L)­Cl] (complex 1, L = 2-methylquinolin-8-olate/complex 2, L = quinolin-8-olate) were synthesized by Vatsa et al for the FADH in the presence of sodium formate (SF). The catalytic activity of the FA/SF solution at different temperatures and concentration ratios was also studied.…”
Section: Fa Decomposition Reaction Pathway Mechanism and Fa Dehydroge...mentioning
confidence: 99%